2015
DOI: 10.1371/journal.pone.0127298
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinarity and Impact: Distinct Effects of Variety, Balance, and Disparity

Abstract: Interdisciplinary research is increasingly recognized as the solution to today’s challenging scientific and societal problems, but the relationship between interdisciplinary research and scientific impact is still unclear. This paper studies the association between the degree of interdisciplinarity and the number of citations at the paper level. Different from previous studies compositing various aspects of interdisciplinarity into a single indicator, we use factor analysis to uncover distinct dimensions of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 53 publications
2
89
2
Order By: Relevance
“…Looking beyond salary and employment status as outcome variables, future longitudinal research should also examine whether interdisciplinary dissertators might show either better or worse or more divergent patterns of research impact. For example, Wang et al (2015)—building on Rinia et al (2001) as well as Tsay and Ma (2003)—show that interdisciplinary research tends to be cited more than other work over longer periods of time (e.g., 13 years post-publication) compared with shorter-terms (e.g., 3 years post-publication). “Sleeping beauty” manuscripts such as those studied by Gorry and Ragouet (2016) similarly help to illustrate the broader trend of lagged success for interdisciplinary research.…”
Section: Discussionmentioning
confidence: 99%
“…Looking beyond salary and employment status as outcome variables, future longitudinal research should also examine whether interdisciplinary dissertators might show either better or worse or more divergent patterns of research impact. For example, Wang et al (2015)—building on Rinia et al (2001) as well as Tsay and Ma (2003)—show that interdisciplinary research tends to be cited more than other work over longer periods of time (e.g., 13 years post-publication) compared with shorter-terms (e.g., 3 years post-publication). “Sleeping beauty” manuscripts such as those studied by Gorry and Ragouet (2016) similarly help to illustrate the broader trend of lagged success for interdisciplinary research.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies take a bottom-up approach, building from measurement of interdisciplinarity for individual articles. The proposed measures are based on the disciplinary profile of the references cited, considering that reference to the preceding literature in various disciplines is as a signal of acquisition and integration of the results of these disciplines (Porter, Cohen, Roessner & Perreault, 2007;Rafols & Meyer, 2010;Wang, Thijs & Glänzel, 2015;Mugabushaka, Kyriakou & Papazoglou, 2016). In particular, Porter & Rafols (2009) used the works published in a cluster of selected journals indexed in the WoS over the period 2007-2011, examining their relative lists of references and identifying the disciplinary areas of the works cited, in terms of: i) number of subject categories (SCs) cited; ii) distribution of the citations among the SCs; iii) similarity or disparity among these SCs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, it prevents from distinguishing between close (or proximal [6]) and remote (or distal) interdisciplinarity and deciphering the relationship of these different dimensions of interdisciplinarity with impact. The effect on short term citations of these different dimensions leads to contradictory results [6, 28, 29], partly due to different decompositions of interdisciplinarity. However, it is suggested that in a long term perspective (citations in a 13-year window), variety and disparity may have a positive effect on impact [28].…”
Section: Discussionmentioning
confidence: 99%
“…The effect on short term citations of these different dimensions leads to contradictory results [6, 28, 29], partly due to different decompositions of interdisciplinarity. However, it is suggested that in a long term perspective (citations in a 13-year window), variety and disparity may have a positive effect on impact [28]. As remote interdisciplinarity is much more demanding from researchers and institutions, it may be worth to use some of these other indicators to analyse specific strategic options.…”
Section: Discussionmentioning
confidence: 99%